Analytical comparison of wideband microstrip log‐periodic and coplanar waveguide antennas. Issue 8 (August 2014) - Tauqeer, Tauseef; Afzal, M. U.; Butt, H. T.; Islam, M.; Tarar, M. A.; Khawaja, Bilal A.
ABSTRACT Customer driven rapid progress in the broadband wireless industry, particularly the evolution of ultra‐wideband communication has rendered an urge toward the design and development of cost‐effective, light weight, and compact wideband antennas. As the requirement arose with the successive development of new techniques, variety of antennas were developed for different applications. Predominately microstrip patch antennas are preferred, because of their added advantage of compact size and less weight in comparison to the other competitors such as flare‐shaped antennas. One of the shortcomings of microstrip antenna is their narrow bandwidth and to address this issue various techniques were explored and presented. Two of the techniques: coplanar waveguide and log‐periodic are analyzed and discussed in this work. Antennas were designed using both, aforesaid, techniques for the same band, fabricated on cost‐effective FR‐4 substrate and then measured using the vector network analyser. Salient features of each type are discussed with expected drawbacks. Simulation of the structures is done in software such as agilent advance design system momentum (MoM based) and CST Microwave Studio(TLM based). Although, these simulators are based on different EM techniques still have produced acceptable simulation results for antennas in comparison with their respective measured results as expected. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1854–1860, 2014